Prenatal developmental origins of behavior and mental health: The influence of maternal stress in pregnancy - Van den Bergh, Bea R.H.; van den Heuvel, Marion I.; Lahti, Marius; Braeken, Marijke; de Rooij, Susanne R.; Entringer, Sonja; Hoyer, Dirk; Roseboom, Tessa; Räikkönen, Katri; King, Suzanne; Schwab, Matthias (Neuroscience and biobehavioral reviews, 2020)
•Maternal psychological distress, life event stress, and objective exposure affect offspring outcome.•Functional and structural brain changes underlie the problems observed in the offspring.•Alterations in stress system, immune system, and gut microbiome play a significant role.•Epigenetic and telomere biology mechanisms are beginning to be explored.•Interventions focused on offspring also need to be guided by knowledge of changes in biological systems. Accumulating research shows that prenatal exposure to maternal stress increases the risk for behavioral and mental health problems later in life. This review systematically analyzes the available human studies to identify harmful stressors, vulnerable periods during pregnancy, specificities in the outcome and biological correlates of the relation between maternal stress and offspring outcome. Effects of maternal stress on offspring neurodevelopment, cognitive development, negative affectivity, difficult temperament and psychiatric disorders are shown in numerous epidemiological and case-control studies. Offspring of both sexes are susceptible to prenatal stress but effects differ. There is not any specific vulnerable period of gestation; prenatal stress effects vary for different gestational ages possibly depending on the developmental stage of specific brain areas and circuits, stress system and immune system. Biological correlates in the prenatally stressed offspring are: aberrations in neurodevelopment, neurocognitive function, cerebral processing, functional and structural brain connectivity involving amygdalae and (pre)frontal cortex, changes in hypothalamo-pituitary-adrenal (HPA)-axis and autonomous nervous system.